Mental health: comparison between gender during work from home / Mohammad Shahrul Aidil, Ahmad Ramadhan Saad and Nurul Haifa Nor Azlan - Aidil, Mohammad Shahrul; Saad, Ahmad Ramadhan; Nor Azlan, Nurul Haifa (2021)
Mental health were health conditions involving changes in emotion, thinking or behavior and for some cases, it might be both. Mental health problems were associated with distress and problems functioning in social, work or family activities. In the year prior to global Covid-19 pandemic, Malaysia was on alert for an outbreak of coronavirus that mainly affecting employees. Many of the employees have to work from home. Employees who work from home do not commute or travel to a central location, such as an ofﬁce building, warehouse, or retail. The shift to virtual communication decreases much-needed personal touch and leads to individual anxiety and sadness, in addition to the stress of needing to master new skills. Spending the entire working day at home with spouses, children, or aged parents is another hardship. A cross sectional study was carried out to identify the signiﬁcant difference between gender towards factors of mental health. A total of 270 respondents were randomly selected among the employees that experience working from home using convenience sampling technique. An online self-reported questionnaire was distributed to random participants. The sections were divided into six parts; demographic sections, work engagements, job demands, home demands, workplace condition and environment and mental health. The independent variable of this study was gender. 188 respondents that have stable mental health condition from the perspective was taken for the samples. Multivariate Analysis of Variance ( MANOVA ) was employed to identify the signiﬁcant difference between gender towards factors of mental health. According to the results, the Wilk’s Lambda’s p-value ( p = 0.008) was less than the signiﬁcance level ( alpha = 0.05). Hence, it can be concluded that there was a signiﬁcant difference between gender towards factors of mental health.